Tuning the spontaneous light emission in phoxonic cavities - E. Almpanis; N. Papanikolaou; G. Gantzounis; N. Stefanou (Journal of the Optical Society of America B, 2012)
The modulation of spontaneous light emission of active centers through elastic waves in Si/SiO2 multilayer phoxonic structures that support dual photonic-phononic localized modes, in the bulk or at the surface, is studied by means of rigorous full electrodynamic and elastodynamic calculations. Our results show that strong dynamic modulation of the spontaneous emission can be achieved through an enhanced acousto-optic interaction when light and elastic energy are simultaneously localized in the same region.